Submarine permafrost in the nearshore zone of the southwestern Kara Sea - Rekant, Pavel; Cherkashev, Georgy; Vanstein, B.; Krinitsky, P. (Geo-Marine Letters, 2005)
The results of seismic studies in the shallow waters of the southwestern Kara Sea show the presence of a seismic unit that can be interpreted as relict submarine permafrost. The permafrost table has a strongly dissected upper surface and is located at a water depth of 5–10 m. A 3D modeling of the permafrost table suggests the presence of relict buried thermodenudational depressions (up to 2 km across) at a water depth of 5–10 m. The depressions may be considered to be paragenetic to thermocirques found at the Shpindler site. Relict thermocirques are completely filled with sediment and not exposed at the sediment surface.